Numerical simulations of wind circumfluence around a Tensairity cylindrical beam and predictions of its response. (March 2019) - Vernarsky, Peter; Tomko, Michal; Soltys, Robert; Kmet, Stanislav
Highlights: Wind circumfluence around the Tensairity cylindrical beam (TCB) is simulated. CFD model and FSI method are used to study wind-induced vibrations of the TCB. Nonlinear FEM is applied to simulate the aeroelastic behavior of the TCB. Vortex-shedding phenomena around the TCB and galloping effects are observed. TCB behaviors obtained by the CFD and FSI models are compared and discussed. Abstract: Numerical simulations of wind circumfluence around Tensairity cylindrical beams and predictions of their response are presented in the paper. An appropriate computational fluid dynamics model (CFD) and a fluid-structure interaction (FSI) method are used to study circumfluent wind fields and wind-induced vibrations of the Tensairity cylindrical beams. Navier-Stokes equations for the incompressible fluid dynamic simulations and FSI analysis of the Tensairity cylindrical beam subjected to the wind flow are applied. Constant and simulated fluctuating wind fields were assigned to the investigated structure. A Spalart-Allmaras (SA) one-equation turbulence model that uses an eddy-viscosity variable with a nonlinear transport equation was applied in the CFD analysis. The finite element method is used to simulate the aeroelastic behavior of the Tensairity cylindrical beam subjected to constant and fluctuating wind effects. Aeroelastic response characterized by wind velocity fields and vortex-shedding phenomena around the cross-section of the inflatable structure are presented. Results obtained from the CFD and FSI analysis were compared. The vortex shedding effects may produce significant lateral (cross-wind) vibrations with nonlinear redistributions of forces and displacements as well as introduce additional deformations to the individual structural members of the Tensairity system. The wind-structure interaction analysis of the Tensairity cylindrical beam revealed, in particular, the sensitivity of the pneumatic structure to vortex induced vibrations with galloping effects.